Simultaneous Determination of Abused Prescription Drugs by Simple Dilute-and-Shoot Gas Chromatography – Flame Ionization Detection (GC-FID). (4th March 2021) - Phonchai, Apichai; Pinsrithong, Sakchaibordee; Janchawee, Benjamas; Prutipanlai, Sathaporn; Botpiboon, Ornchuma; Keawpradub, Niwat
Abstract: Lean cocktail is an improvised drink that contains prescription drugs. It is prepared and abused primarily by young people and may cause serious long-term and short-term health problems. This study sought to develop a method of simultaneously determining the commonly abused prescription drugs in lean cocktail. To achieve this objective, gas chromatography with flame ionization detection (GC-FID) was employed with a dilute-and-shoot sample preparation technique. The chromatographic method was optimized and fully validated, and all analytes were well separated within 19 min. The responses were linear across the concentration range from 2.5 to 1000 µg mL −1 ( r 2  > 0.99), and the limits of detection and quantitation were 1.25 to 2.50 µg mL −1 and 2.5 to 55.0 µg mL −1, respectively. The accuracy and precision were from 91% to 110% and 4.1% to 8.7% relative standard deviation, respectively. The sample dilution from 2- to 10-fold and the matrix had no effect upon the analysis. Robustness testing revealed that the method is reliable. The developed method has identified tramadol and promethazine as the typically abused prescription drugs in the analyzed lean cocktail samples. These findings indicate that this new method is simple and reliable and has potential benefits for the forensic analysis of lean cocktail samples.